På sporet af en mytes oprindelse - Leopold, Anita Maria (Religionsvidenskabeligt Tidsskrift, 2001)
This article is a rereading of Friedrich Max Müller’s theory of the origin and growth of religion and mythology in the light of modern cognitive theories. The intention of this research is to draw attention to Max Müller’s linguistic and cognitive hypothesis of mythology and religion and compare it to modern cognitive theories presented by Mark Turner, Gilles Fauconnier, George Lakoff and Mark Johnson. In the theory of Max Müller, notions such as ‘myth being a disease of language’ and ‘man’s propensity to religion’ originate from a certain ‘mental faculty’, which reveals an ontologically distinct definition of religion. According to Max Müller, myth is the result of the defective attempt of early language to classify the surrounding world of man. These theories, which have been considered idiosyncratic and useless, appear more plausible in the light of current cognitive linguistics, and Max Müller’s intuitions are viewed in the light of these recent theories.